2020
DOI: 10.1088/1361-6641/ab7b0b
|View full text |Cite
|
Sign up to set email alerts
|

Non-volatile memory application of glancing angle deposition synthesized Er2O3 capped SnO2 nanostructures

Abstract: An Er 2 O 3 capped SnO 2 nanostructure (NS) based memory device was synthesized on Si substrate by glancing angle deposition technique. Field emission scanning electron microscopy and transmission electron microscopy were used to verify the formation of the Er 2 O 3 capped SnO 2 NS. The Er 2 O 3 capped SnO 2 NSs were polycrystalline in nature as obtained from selected area electron diffraction analysis. Au metal contact was deposited over the Er 2 O 3 capped SnO 2 NS to fabricate a Au/Er 2 O 3 -SnO 2 /Si memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…These types of oxides might be utilized in future nonvolatile memory applications. Figure a,b demonstrates the band diagrams indicating the program mode and erase mode, respectively, while Figure c–e represents the relation between threshold voltage versus applied voltage, threshold voltage versus P/E cycles, and threshold voltage versus time (retention) for the Er 2 O 3 -capped SnO 2 NS and bare SnO 2 NWs at room temperature, respectively. Table indicates a few specific rare earth oxides which are utilized in various memory devices.…”
Section: Electronic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of oxides might be utilized in future nonvolatile memory applications. Figure a,b demonstrates the band diagrams indicating the program mode and erase mode, respectively, while Figure c–e represents the relation between threshold voltage versus applied voltage, threshold voltage versus P/E cycles, and threshold voltage versus time (retention) for the Er 2 O 3 -capped SnO 2 NS and bare SnO 2 NWs at room temperature, respectively. Table indicates a few specific rare earth oxides which are utilized in various memory devices.…”
Section: Electronic Devicesmentioning
confidence: 99%
“…The plot of threshold voltage at room temperature with respect to (c) sweeping voltage (both for Er 2 O 3 -capped SnO 2 nanostructure and bare SnO 2 NWs), (d) P/E cycles (endurance), and (e) time (retention). Reproduced with permission from ref . Copyright 2020 IOP Publishing Ltd.…”
Section: Electronic Devicesmentioning
confidence: 99%
“…Hence, SnO 2 is found to be an appealing contender for upcoming non-volatile memory equipment. 30 Moreover, recent studies have indicated that SnO 2 is capable of demonstrating threshold-switching phenomena. 31 The phenomenon of threshold switching refers to the rapid transition of a material from high resistance state (HRS) to a low resistance state (LRS) upon the attainment of a speci c threshold voltage.…”
Section: Introductionmentioning
confidence: 99%